Microscopic Warriors - Immunomodulatory and Anticancer Properties of Fungi - BODERA, MAGDALENA; SZYDLOWSKI, RADOSLAW; KAZMIERSKA, ANNA; HAMERLA, ANNA; PORWOLIK, HANNA; SKOTARSKI, MAREK; GAWRON, JULIA; RABSTEIN, DOMINIK; GOSCINIEWICZ, PIOTR (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Fungi, comprising a vast and diverse kingdom, are increasingly recognized for their bioactive compounds with potential health benefits, including anticancer properties. Mushrooms, rich in polysaccharides, proteins, vitamins, and trace elements, have traditionally been used for disease prevention and treatment, notably cancer. Materials and Methods: A thorough review of the literature was carried out using the PubMed and Google Scholar databases, with search terms focusing on mushrooms and different types of cancer. The analysis included observational studies, meta-analyses, and experimental research that examined the relationship between mushroom consumption and cancer risk or progression. Aim of the Study: to systematically review existing literature on the relationship between mushroom intake and cancer risk, focusing on breast, prostate, gastric, colorectal, and lung cancers, and to discuss the immunomodulatory and therapeutic effects of fungal bioactive compounds. Results: Evidence indicates a notable negative correlation was observed between mushroom intake and the risk of specific types of cancer particularly breast and prostate cancer, with some studies highlighting immunomodulatory effects of β-glucans and other fungal compounds. Mushroom consumption is linked to lower overall mortality and reduced risk of breast cancer, especially in populations of Asian origin and postmenopausal females. While results are more consistent in Asian cohorts, data from Western countries are inconclusive, suggesting the need for further research. Mushroom extracts such as PSK have shown promise as adjunctive therapies in gastric and colorectal cancers. Conclusion: Overall, mushrooms represent a valuable dietary component with potential cancer-preventive and supportive therapeutic roles, warranting further clinical investigation.